INTEGRATING CSR AND GREEN ACCOUNTING: IMPACT ON CORPORATE FINANCIAL PERFORMANCE IN INDONESIA - Bahtiar Effendi (PT. ZILLZELL MEDIA PRIMA, 2025)
This study investigates the impact of Corporate Social Responsibility (CSR) and Green Accounting on the financial performance of companies in emerging markets, focusing on the Indonesian manufacturing sector during the period 2020–2024. A total of 220 manufacturing firms listed on the Indonesia Stock Exchange (IDX) were selected using purposive sampling, based on the availability of sustainability and annual reports. The analysis employed multiple linear regression with the support of EViews 12 software to examine the relationship between the independent variables (CSR and Green Accounting) and financial performance. The findings reveal that both CSR and Green Accounting have a significant positive influence on financial performance, indicating that firms engaging in socially and environmentally responsible practices are likely to achieve better financial outcomes. These results highlight the strategic importance of integrating sustainability initiatives into corporate operations. Future research is recommended to explore additional variables and extend the analysis across different sectors or timeframes.